2018
DOI: 10.1371/journal.pone.0201664
|View full text |Cite
|
Sign up to set email alerts
|

Call and be counted! Can we reliably estimate the number of callers in the indri's (Indri indri) song?

Abstract: Estimating the number of animals participating in a choral display may contribute reliable information on animal population estimates, particularly when environmental or behavioral factors restrict the possibility of visual surveys. Difficulties in providing a reliable estimate of the number of singers in a chorus are many (e.g., background noise masking, overlap). In this work, we contributed data on the vocal chorusing of the indri lemurs (Indri indri), which emit howling cries, known as songs, uttered by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…When we considered songs emitted by 4 singers, our results were inconsistent possibly because of the small sample ( N = 5). Songs with a chorus size exceeding 3 indris are rare (Torti et al 2018) because groups are usually smaller (Bonadonna et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When we considered songs emitted by 4 singers, our results were inconsistent possibly because of the small sample ( N = 5). Songs with a chorus size exceeding 3 indris are rare (Torti et al 2018) because groups are usually smaller (Bonadonna et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In order to address this issue, we designed a decision tree shown in figure 1 to aid researchers in selecting papers to begin their own investigations into the field. Torti et al [88] implemented a method known as the Acoustic Complexity Index to estimate the number of lemurs (Indri indri) taking part in a choral display in a tropical environment. They found that relatively simple spectrographic analysis was sufficient when identifying up to three singers, but for larger numbers of animals the Acoustic Complexity Index [89] performed well, positively correlating with the number of animals in the environment.…”
Section: Automated Acoustic Monitoring In Ecology and Conservationmentioning
confidence: 99%
“…royalsocietypublishing.org/journal/rsif J. R. Soc. Interface 16: 20190225 methods to determine the number of animals taking part in a choral display [88,90] or in the application of acoustic indices to monitoring biodiversity [90]. This is one of the major challenges bioacoustics faces in terms of its application to animal welfare.…”
Section: Anthropogenic Noisementioning
confidence: 99%
“…Songs can be emitted as duets-when only the members of the reproductive pair sing together-or as choruses when one or more non-reproductive members join the parents when singing. All the individuals within a family group, aged one year or above, can join the chorus (Torti et al 2018;De Gregorio et al submitted R1).…”
Section: Introductionmentioning
confidence: 99%